The Drama of coronation: medieval ceremony in early modern England - Hunt, Alice (Cambridge Univ. Press, 2010)
Introduction : The "idol" ceremony of coronation -- Why crown a king? : Henry VIII and the medieval coronation -- "Come my love thou shalbe crowned": the drama of Anne Boleyn's coronation -- "But a ceremony" : -- Edward VI's reformed coronation and John Bale's King Johan -- "He hath sent marye our soveraigne and quene" : England's first queen and respublica -- "A stage wherin was shewed the wonderfull spectacle" : Representing Elizabeth I's coronation -- Epilogue: "presume not that I am the thing I was"